2005
DOI: 10.1101/gr.3840605
|View full text |Cite
|
Sign up to set email alerts
|

Origin and primary dispersal of the Mycobacterium tuberculosis Beijing genotype: Clues from human phylogeography

Abstract: We suggest that the evolution of the population structure of microbial pathogens is influenced by that of modern humans. Consequently, the timing of hallmark changes in bacterial genomes within the last 100,000 yr may be attempted by comparison with relevant human migrations. Here, we used a lineage within Mycobacterium tuberculosis, a Beijing genotype, as a model and compared its phylogeography with human demography and Y chromosome-based phylogeography. We hypothesize that two key events shaped the early his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 42 publications
7
155
1
2
Order By: Relevance
“…The strains of Bj-MG1 have an intact RD181, whereas all of the other Beijing strains harbor a specific deletion in this region. The strains of Bj-MG3 harbor an insertion of IS6110 in the NTF region and correspond to the previously defined "modern" Beijing subtype (27). Consequently, the Bj-MG1, Bj-MG2, and other Beijing strains correspond to the "ancient" Beijing subtype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strains of Bj-MG1 have an intact RD181, whereas all of the other Beijing strains harbor a specific deletion in this region. The strains of Bj-MG3 harbor an insertion of IS6110 in the NTF region and correspond to the previously defined "modern" Beijing subtype (27). Consequently, the Bj-MG1, Bj-MG2, and other Beijing strains correspond to the "ancient" Beijing subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a general East Asian/Chinese origin of this strain family was suggested based on its highest prevalence rate and/or highest level of diversity in those regions (18,27,36,50). In the current study, we provided further evidence and proposed a southern East Asia origin of Beijing family, which is consistent with the latest anthropological evidence about the colonization and migrations of modern human in East Asia (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El genotipo Central-Asia (CAS) o Delhi, localizado en el Medio Oriente, Asia Central, Europa y Australia, lo que lo vincula con los inmigrantes del sur de Asia 1 . El genotipo X, prevalente en América del Norte y regiones de América Central sugiriendo una ascendencia anglosajona o incluso afro-americana 1,6 y por último el genotipo Beijing, endémico y con un claro predominio en ciertas regiones del extremo Oriente, Asia y Oceanía, exceptuando India subcontinental y Sudáfrica 1,8,9 , se ha asociado a alta transmisibilidad, multi-resistencia 8,10 y mayor poder patógeno asociado a la baja inducción de citoquinas inflamatorias, lo que permitiría un mayor crecimiento intracelular del cMtb 2,11 . En los Estados Unidos de América, específicamente en Nueva York, en el año 1991, durante un brote que afectó a ocho pacientes www.sochinf.cl con TBC resistente a isoniacida, rifampicina, etambutol, estreptomicina, kanamicina, etionamida y rifabutina, se identificó el genotipo "W", que fue posteriormente asociado a otros cinco brotes en hospitales del área de Nueva York.…”
Section: Introductionunclassified
“…A recent report suggested that the modern Beijing sublineage, which has high transmissibility, is currently increasing in Japan (12). Furthermore, the modern sublineage is considered to be more virulent and to have higher fitness in human hosts than the ancient sublineage (6,(11)(12)(13). Therefore, it is essential to continuously monitor the population shift for a long period in Mie Prefecture.…”
mentioning
confidence: 99%